Association of matrix metalloproteinase gene polymorphisms with different biological subtypes of breast cancer - Nadezhda V. Pavlova; Irina V. Ponomarenko; Mikhail I. Churnosov (IP Berlin A.V., 2022)
Aim. To investigate the associations of matrix metalloproteinase (MMP) MMP3 (rs679620), MMP8 (rs1940475), and MMP9 (rs17576 and rs3787268) gene polymorphisms with different biological subtypes of breast cancer (BC). Materials and methods. The study sample consisted of 285 patients with BC of various biological subtypes (luminal A and B [n=153], triple negative [n=108], and HER2 positive [HER2+, n=24]) and 746 females in the control group. Genotyping of four polymorphic sites of MMP3 (rs679620), MMP8 (rs1940475), and MMP9 (rs17576 and rs3787268) genes was performed in the study groups. Results. The role of MMP gene polymorphisms in the BC development of various biological subtypes differs. The c.836 AG MMP9 polymorphism (rs17576, the odds ratio is 0.670.71 for the G allele) has a protective effect on the development of luminal A- and B-subtypes of BC; susceptibility to triple-negative BC is associated with the polymorphic site c.1331-163 GA MMP9 (rs3787268, OR 4.51 for genotype AA), and two polymorphisms of the MMP3 (c.133 TC, rs679620, OR 0.460.49 for T allele) and MMP8 (c.259 TC, rs1940475, OR 0.370.48 for T allele) genes are associated with HER2+ BC development. According to the in silico data, the above polymorphisms have pronounced functional effects in organs and tissues that are pathogenetically significant for the disease, including the target organ, the breast. Conclusion. The c.836 AG MMP9 (rs17576) polymorphism is associated with luminal A- and B-subtype of BC; c.1331-163 GA MMP9 (rs3787268) is associated with triple negative BC, and c.133 TC MMP3 (rs679620) and c.259 TC MMP8 (rs1940475) are involved in HER2+ BC development.